2010
DOI: 10.3109/08916931003774954
|View full text |Cite
|
Sign up to set email alerts
|

Epitopes, immunoglobulin classes and immunoglobulin G subclasses of calsequestrin antibodies in patients with thyroid eye disease

Abstract: A number of serum autoantibodies are associated with thyroid eye disease (TED), including those reactive against the calcium binding protein calsequestrin (CASQ). There are two isoforms of CASQ namely; CASQ1, found in skeletal, including extra ocular, muscle, and CASQ2, found in cardiac muscle. We determined (i) the reactivity profiles of CASQ1 and CASQ2 antibodies and (ii) the immunoglobulin (Ig) classes and IgG subclasses of CASQ1 antibodies, using enzyme-linked immunosorbent assay. Of the 20 patients with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Patients with Graves' disease (a thyroid disease) show increased mRNA levels of both the CASQ1 and CASQ2 genes in thyroid tissue 197 . Unlike normal subjects, patients with Graves' hyperthyroidism without ophthalmopathy and Hashimoto's thyroiditis with or without ophthalmopathy show significant levels of autoantibodies against CASQ1 in the serum 198,199 . The acute induction of hyperthyroidism in the rabbit soleus muscle increases the mRNA level of CASQ1 200 .…”
Section: Casq1-related Diseasesmentioning
confidence: 94%
“…Patients with Graves' disease (a thyroid disease) show increased mRNA levels of both the CASQ1 and CASQ2 genes in thyroid tissue 197 . Unlike normal subjects, patients with Graves' hyperthyroidism without ophthalmopathy and Hashimoto's thyroiditis with or without ophthalmopathy show significant levels of autoantibodies against CASQ1 in the serum 198,199 . The acute induction of hyperthyroidism in the rabbit soleus muscle increases the mRNA level of CASQ1 200 .…”
Section: Casq1-related Diseasesmentioning
confidence: 94%
“…In our recent studies we have shown that calsequestrin antibodies are sensitive and specific markers of extra ocular muscle inflammation and damage, not only in patients with Graves' disease [8,9] but also in those with Hashimoto's thyroiditis [4] and transient (sub acute, silent) thyroiditis [14]. In addition, we have recently shown that calsequestrin may be a target of T lymphocyte-mediated immune responses in patients with Graves' ophthalmopathy [25]. While antibodies against the eye muscle antigens flavoprotein (Fp) and G2s are also linked to ophthalmopathy they are less specific and sensitive markers of eye muscle damage [3,9,20].…”
Section: Discussionmentioning
confidence: 99%
“…In 2001 Porter et al [24] demonstrated by micro-array technology that calsequestrin was expressed 4.7 times more in eye muscle than other skeletal muscle, providing a possible explanation for the localisation of a skeletal muscle reaction in the orbit. Cardiac calsequestrin (CASQ2) is encoded by a different gene but the two proteins share 60% homology; antibodies targeting CASQ2 do not cross react with calsequestrin [25]. Another orbital antigen of interest is the fibroblast cell membrane protein collagen XIII.…”
Section: Discussionmentioning
confidence: 99%
“…One group failed to detect Tg in the extraocular musculature (Kodama, et al 1984). They have proposed that extraocular muscles rather than fatty connective tissue are the primary targets in TAO, concluding that muscle proteins harbor the important immunogenic determinants (de Haan, et al 2010). Their contention has not been supported by convincing experimental evidence.…”
Section: Search For An Orbital Autoantigen In Taomentioning
confidence: 99%